Conditions of Custody and its Implications in Islamic Jurisprudence - Rahman , Basim (Islamic Sciences Journal, 2023)
This study aims to show the importance of a suitable environment for the child and taking care of him, and that he must live in the confinement of his parents and their protection, and the effect of custody on Looking after the child and the role of the mother in that, and the negative consequences that result if he loses this nursery. So custody is the upbringing of those who are not independent by doing What works for him and protects him from what harms him, such as undertaking to wash his body, clothes, ointments, and eyeliner, tie him in the cradle, and so on: Among the general conditions of custody that must be available in the incubator, whether he is a man or a woman, is, Islam and maturity, The conditions for women are not to be married to a foreigner, and the conditions for men to have with the incubator, whether the father or other incubator, someone who takes custody of the child. The most important reasons that lead to the loss of custody are the abandonment of the mother from the child, as well as the divorce and apostasy from Islam.